ПРОДОЛЬНЫЕ ДЕФОРМАЦИИ УКОРОЧЕНИЯ СТАЛЕЖЕЛЕЗОБЕТОННЫХ КОНСТРУКЦИЙ ПРИ СЖАТИИ ОТ НЕПРОДОЛЖИТЕЛЬНЫХ НАГРУЗОК - Конин, Денис (International Journal for Computational Civil and Structural Engineering, 2025)
Determination and investigation of longitudinal deformations of shortening of steel-reinforced concrete structures is an important step in the calculation of complex spatial schemes of buildings. Ignoring these deformations can make it difficult to operate the facility and, in some cases, lead to the failure of adjacent structures. The study of longitudinal deformations of shortening of steel-reinforced concrete structures has not been given due attention before. The longitudinal deformations of shortening for steel-reinforced concrete compressed elements using a large range of heavy concretes (from B25 to B80) and percentages of reinforcement (from 0 to 22%) are estimated. The deformations were calculated. The analysis of experimental data obtained during testing of conditionally centrally compressed models of columns of steel-reinforced concrete structures is presented. It is shown that the existing diagrams of concrete work do not accurately describe the work of a composite steel-reinforced concrete structure, it is its shortening and reduced rigidity. When the structure is compressed, concrete loses its destruction at earlier stages of loading than it would be for concrete or reinforced concrete. This fact is caused by the stress-strain state of the concrete section separated by steel elements, as well as the effects of early detachment and slippage along the «steel-concrete» contact surface. It is necessary to use a system of additional coefficients to eliminate the established discrepancy in determining the magnitude of longitudinal deformation (shortening) under the action of short-term loads and experimentally obtained data. These coefficients should increase the theoretical value of the expected relative deformations and consider the features of the work of conventional and high-strength concrete as part of compressible steel-reinforced concrete structures. When determining the stiffness values for steel-reinforced concrete structures under the action of short-term loads and bringing the calculated longitudinal stiffness to a value close to experimental data, it is proposed to introduce an additional coefficient. This coefficient further reduces the longitudinal rigidity of the structure depending on the stress level in concrete and steel. Определение и исследование продольных деформаций укорочения сталежелезобетонных конструкций является важным этапом в вопросе расчета сложных пространственных схем зданий, поскольку их игнорирование может затруднить эксплуатацию объекта и, в некоторых случаях, привести к выходу из строя примыкающих конструкций. Ранее исследованию продольных деформаций укорочения сталежелезобетонных конструкций не уделялось должного внимания. Дана оценка продольных деформаций укорочения для сталежелезобетонных сжатых элементов с применением большого диапазона тяжелых бетонов (от В25 до В80) и процентов армирования (от 0 до 22%), произведен расчет деформаций. Представлен анализ экспериментальных данных, полученных при испытании условно центрально сжатых моделей колонн сталежелезобетонных конструкций. Показано, что существующие диаграммы работы бетона не вполне точно описывают работу составной сталежелезобетонной конструкции, в частности, ее укорочение и приведенную жесткость. При работе конструкции на сжатие бетон разрушается на более ранних этапах нагружения, чем это было бы для бетона или железобетона. Этот факт вызван напряженно-деформированным состоянием разделенного стальными элементами бетонного сечения, а также эффектами раннего отслоения и проскальзывания по контактной поверхности «сталь-бетон». Для того, чтобы устранить установленное разночтение в определении величины продольной деформации (укорочения) при действии кратковременных нагрузок и экспериментально полученных данных, необходимо использовать систему дополнительных коэффициентов, которые должны увеличивать теоретическую величину ожидаемых относительных деформаций, а также должны учитывать особенности работы бетонов обычной и высокой прочности в составе сжимаемых сталежелезобетонных конструкций. При определении значений жесткостей для сталежелезобетонных конструкций под действием кратковременных нагрузок и приведении расчетной продольной жесткости к величине, близкой к экспериментальным данным, предложено ввести дополнительный коэффициент, который дополнительно понижает продольную жесткость конструкции в зависимости от уровня напряжений в бетоне и стали.